Analysis of students’ mathematical communication ability on student learning styles - Asgafi, Alwi; Anwar, Muhammad Saidun; Choirudin, Choirudin; Darmayanti, Rani; Usmiyatun, Usmiyatun (AMCA Journal of Science and Technology, 2023)
Students’ mathematical communication ability is their ability to communicate mathematical concepts orally and in writing. The inability of students to fulfill indicators of their ability to relate something that happens to mathematical ideas, in addition to the failure of students to explain concepts, situations, and mathematical relationships, is the root cause of students’ low ability to communicate mathematically. This study aimed to determine the mathematical communication abilities of students whose learning styles ranged from high to low. This research is descriptive qualitative research. A qualitative approach was chosen because this study used written and oral data. Class VII students of MTs Ma’arif Roudlotut Tholibin Metro, consisting of six male students and ten female students with various learning styles, were the subjects of this study. This study used interviews, learning-style questionnaires, and tests to collect data. Sources of information were obtained from the results of surveys on learning styles, tests, and interviews acquired from students. After being seen and researched, the results show that different learning styles have different abilities in mathematical communication. Based on student learning styles, the test scores for auditory learning styles are 77, visual 65, kinesthetic 62.5, and read and write 70. Therefore, it can be concluded that compared to students who use other learning styles, students with visual learning styles have better mathematical communication abilities.